Criticism and the Concept of Sharia Deconstruction in the Thoughts of Abdullah Ahmed Naim - Arrizqah Bariroh; Achmad Fageh (al-Afkar, Journal For Islamic Studies, 2025)
Thoughts about Sharia in Islam have experienced a significant evolution from its early days to the current contemporary era. Abdullah Ahmed Naim, a leading thinker in contemporary Islamic studies, offers a provocative perspective through his deconstruction of Sharia. An-Naim argues that Sharia should be seen as a product of human history and culture, not a static divine law. With a deconstructive approach, An-Nuaim highlights the importance of contextualizing Islamic law, emphasizing that the interpretation of Sharia must be adapted to continuously developing social needs and realities. This view invites in-depth discussion about the relevance and application of Sharia in the modern world. This research uses a descriptive qualitative method with a library study approach, where data is collected through collection from various academic sources, including books, journal articles and An-Na'im's own works. The analysis was carried out by reducing data, presenting the data, and continuing with drawing conclusions. The results of this research are that it can be seen that this approach is not only relevant for legal reform but also has significant implications for Islamic studies and society's understanding of pluralism in the legal context. Through the deconstruction of sharia, there is hope to create an Islamic legal system that is more just, inclusive and responsive to the challenges of the times.